Efektifitas Pembelajaran Menggunakan Media Program Microsoft Powerpoint Terhadap Hasil Belajar Siswa Mata Pelajaran TITL Kelas X - Ismawati Ismawati; Fria Pahlevi; M. Rizky Pangestu (Universitas Baturaja, 2023)
The purpose of this research is to know the effectiveness of using microsoft powerpoint learning for the students in the subject TITL class X. This research is quantitative research with the experimental methods, with a design research one-group pretest-posttest design. Population of 64 people and samples of 22 class X. The data that has been based on the result analysis conducted then we can conclude the effectiveness of learning program using media for the microsoft powerpoint student learning on the subjects of TITL class X. Effectiveness of media learning program microsoft powerpoint demonstrable from the testing hipotestis t-hitung indicating that greater than t-tabel 8,06 >2,08